Efektivitas TGT dan TSTS dalam Meningkatkan Komunikasi dan Problem Solving Matematis Siswa - Rangkuti, Sakdiah Aini; Thahara, Malika; Tobing, Talitha Eriliyah Wardhana; Maharani, Israq (OMEGA: Jurnal Keilmuan Pendidikan Matematika, 2025)
This study aims to analyze the improvement of students' mathematical communication and problem-solving skills through the implementation of cooperative learning models, namely Teams Games Tournament (TGT) and Think Pair Share (TPS). Data were collected through mathematical communication skill tests, mathematical problem-solving tests, observations, and interviews. The results indicate a significant improvement in students' mathematical communication and problem-solving skills using TGT and TPS models compared to conventional teaching methods. The TGT group showed an average increase in pretest and posttest scores of 19.8 points in communication skills and 21.9 points in problem-solving skills. The TPS group showed an average increase of 18.9 points in communication and 19.9 points in problem-solving. Meanwhile, the control group showed an average increase of only 8.2 points in communication and 9.4 points in problem-solving. The study recommends the broader application of cooperative learning models and teacher training to enhance teaching effectiveness.